(أثر تفاسير وشروح المالكية في توجيه قضية الطلاق في المجتمع الليبي (مدينة سبها نموذجاً - Ibrahim Salem Abdusalam Alsmar Al-Hodiri
This study aims to clarify the facts about Quranic and prophetic approach and explain it with regard to divorce and its treatment. In addition to that clarifying the effect of Malikies commentaries in directing the divorce phenomenon, and revealing the important role of holy Quran and prophetic approach to protect the Islamic communities from moral decay, disintegration and displacement and prevention the divorce phenomenon, as well as revealing the impact of clans and tribes on wedlock such as early marriage and parents interference in couple’s life. The study also explained the role of Libyan media and the mosques of Sabha city in increasing the awareness of people about the negative impact of divorce on the community. The researcher used the descriptive methodology by following the interpretations of Malikies, and also used the survey approach through notes and questionnaires distributed to different social groups inside the Libyan community and selecting Sabaha city as the case study. The study found that early marriage has a direct effect on ending the marriage relationship and then lead to divorce, and showed the ignorance of most participants in understanding Malikies commentaries with regard to divorce, and the main reason for this misunderstanding is due to the influence of tribal customs and neglecting the social role of Islamic religion. The survey of the study showed that polygamy is the main factor that end and damage the wedlock and increasing the rate of divorce because the tribal mentality does not understand the main legal concepts of polygamy, and most of participants showed the failure of Libyan media in spreading the Islamic culture to the Libyan people, and the failure of mosques’ preacher in increasing the awareness about divorce among Libyan people, most of the participants tended to affirm the negative tribal role where parents take the task of searching good wife for their son, furthermore the parental interference that increases this negative role and ends the marriage relationships in most of the cases unlike the western communities.